An investigation into the anxiolytic properties of melatonin in humans - McCallaghan, Johannes Jacobus (Rhodes University, Faculty of Pharmacy, Pharmacy, 1999)
The purpose of this project was to investigate the role of melatonin in the pathophysiology of anxiety in humans. The literature study confirmed the intimate relationship between serotonin and melatonin. Melatonin is not only able to act as an agonist (in physiological concentrations) and an antagonist (at higher concentrations) on serotonin receptors but via control of brain pyridoxal kinase activity might have an effect on GABA, serotonin, dopamine and norepinephrine synthesis. A clinical trial to investigate melatonin's effect on anxiety in humans was conducted as a pilot study. Thirty patients complaining of anxiety participated in a liN of 1" double blind placebo controlled trial. During the experiment each subject was thus exposed to melatonin and a placebo for a week at a time on two occasions. During the first phase of the experiment, (Pair '1) patients showed a statistically significant reduction in their anxiety levels during the first period (P1P1), which was not the case during the second period (P1P2). The improvement however continued during the second phase of the experiment (Pair 2) so that there was also a statistically significant improvement during P 2 P 2 (Period 2 / Pair 2) when placebo was administered. It could not conclusively be shown that melatonin was responsible for the improvement in the patients' anxiety. The explanation for these results suggests thelt the improvement was due to a: 1) placebo effect throughout, 2) psychotherapeutic effect due to contact with a clinician, 3) melatonin induced phase shift in the patient's endogenous melatonin response curve, 4) combination of all 3 options. This pilot study lays the groundwork for a much more exhaustive study in which the melatonin of the patients is determined before melatonin is administered, the role of the clinician is clarified and the most appropriate time for melatonin administration is sought .
Keywords: Melatonin; Pineal gland -- Secretions